(untitled) (Swiss Medical Weekly, 2019)
OBJECTIVE Behçet’s syndrome is a rare systemic autoimmune/autoinflammatory disease affecting mucocutaneous tissues, the skin and the eyes, as well as the joints, the central nervous system, the gastrointestinal tract and blood vessels. Because of the lack of clinical data in Switzerland, the aims of this cohort study were to calculate the disease prevalence and to analyse the disease manifestations and the immune-suppressive medication. METHODS Data were extracted from 52 patient charts. Thereafter, all patients were interviewed with a questionnaire and 46 had an additional physical examination and laboratory analyses. For calculation of prevalence, data of the national statistical bureau were used. RESULTS A disease prevalence of 4.03/100,000 inhabitants was calculated. The mean delay between first disease manifestation and diagnosis was 8 years. It was 2 years longer for Swiss than for non-Swiss individuals (p = 0.45). The time intervals between diagnosis and occurrence of different organ manifestations ranged from +8 to −11 years. There was no difference in organ involvement between different ethnicities. Colchicine was prescribed for 52% of patients only, whereas tumour necrosis factor (TNF) inhibitors and glucocorticoids were most frequently prescribed (80 and 64%, respectively). In almost half of the patients, TNF blockers could be stopped and replaced by conventional immunosuppressive drugs. CONCLUSION The data from this cohort of Behçet’s syndrome patients, the largest in Switzerland, documents a prevalence higher than anticipated. The diagnostic delay underlines an urgent need to improve awareness of the disease and allow timely treatment.